Medieval Britain and Ireland in 2023: Portable Antiquities Scheme - Naylor, J (Taylor & Francis, 2024)
Report on medieval finds reported to the Portable Antiquities Scheme in 2023 including individual the sections 'Focus on coinage in 2023', 'Focus on non-numismatic finds in 2023', and a research note 'A rare pilgrim badge of St John Lateran, Rome' (by Robert Webley)